Chitosan-Based Composite Materials for Prospective Hemostatic Applications - Hu, Zhang; Zhang, Dong-Ying; Lu, Si-Tong; Li, Pu-Wang; Li, Si-Dong (Marine drugs, 2018)
Effective hemostasis is vital to reduce the pain and mortality of patients, and the research and development of hemostatic materials are prerequisite for effective hemostasis. Chitosan (CS), with good biodegradability, biocompatibility and non-toxicity, has been widely applied in bio-medicine, the chemical industry, the food industry and cosmetics. The excellent hemostatic properties of CS have been extensively studied. As a result, chitosan-based composite hemostatic materials have been emerging. In this review, the hemostatic mechanism of chitosan is briefly discussed, and then the progress of research on chitosan-based composite hemostatic materials with multiple forms such as films, sponges, hydrogels, particles and fibers are introduced. Finally, future perspectives of chitosan-based composite hemostatic materials are given. The objective of this review is to provide a reference for further research and development of effective hemostatic materials.